Analisis Perkembangan Usaha Kecil Menengah (UKM) Setelah Mendapatkan Pembiayaan Gardhul Hasan dari BMT Mandiri Sejahtera Karangcangkring Jawa Timur Cabang Campurejo - Shofi Ayundah; Mustika Indah Puspa Diana; Ahmad Afan Zaini (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
Small and Medium Enterprises (SMEs) in Campurejo in buying and selling activities are still difficult to sell various types of fish, vegetables and also fruits in large quantities. On average, each fish seller can only sell 2 or 3 types of fish, as well as vegetable and fruit sellers. Seeing the problems of the development of SMEs that still lack further attention, this development research was carried out. This research is a development research, which aims to develop the development of SMEs after obtaining Qordhul Hasan financing, especially fish, vegetable and fruit traders. The formulation of this research consists of: 1) How is the Management Model of Small and Medium Enterprises (SMEs) in the Campurejo village market. 2) How is the development of small and medium enterprises after getting Qordhul Hasan financing from BMT Mandiri Sejahtera Campurejo. This study uses a qualitative research type using a descriptive approach. The results of this study are to determine: 1. Small and Medium Enterprises (UKM) Management Model in the Campurejo village market, which include: a) To trade fish in the small traders market does not require a lot of capital, because most small fish traders only requires market land rent of Rp. 150,000, - per month, and every day there is still another withdrawal of Rp. 2,000, - / day. And money to buy merchandise in the form of the fish. b) To buy vegetables every day it is only around Rp. 90,000, - to Rp. 120,000, -. Meanwhile, to buy fruit, they spend around IDR 1,000,000/purchase.2. The development of small and medium enterprises after obtaining financing from Qordhul Hasan from BMT Mandiri Sejahtera Campurejo, which include: a) Small and Medium Enterprises (SMEs), selling fish business. This business can continue to run smoothly in trading and buying and selling fish in the market. Before applying for financing, Qordhul Hasan earned a net profit of Rp. 50,000 after doing the financing to Rp. 80,000. b) Small and Medium Enterprises (SMEs), businesses selling vegetables. These businesses can continue to run smoothly in trading and buying and selling vegetables in the market. Before applying for financing, Qordhul Hasan earned a net profit of Rp. 100,000 after doing the financing to Rp. 150,000.